2018
DOI: 10.1073/pnas.1807704115
|View full text |Cite
|
Sign up to set email alerts
|

Control of CCND1 ubiquitylation by the catalytic SAGA subunit USP22 is essential for cell cycle progression through G1 in cancer cells

Abstract: SignificanceThe deubiquitylase USP22 is frequently overexpressed in cancer and contributes to tumorigenesis by driving cell cycle progression. Current models define USP22 as functional mediator of gene regulation and chromatin modification, working within the SAGA transcriptional cofactor complex. Here we report a catalytic role for USP22 distinct from its well-characterized transcription regulatory capacity. USP22 directly stabilizes the essential G1-cyclin, CCND1, protecting it from proteasome-mediated degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 70 publications
3
78
0
Order By: Relevance
“…Usp22 depletion in cultured cells has been associated with G1/M cell cycle arrest (Gennaro et al, 2018;Zhang et al, 2008b), proliferation defects (Atanassov and Dent, 2011), p53-dependent apoptosis (Lin et al, 2012) and blockage of stem cell differentiation (Sussman et al, 2013). Although no defects in proliferation or increased cell death were observed at E9.5 ( Fig.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Usp22 depletion in cultured cells has been associated with G1/M cell cycle arrest (Gennaro et al, 2018;Zhang et al, 2008b), proliferation defects (Atanassov and Dent, 2011), p53-dependent apoptosis (Lin et al, 2012) and blockage of stem cell differentiation (Sussman et al, 2013). Although no defects in proliferation or increased cell death were observed at E9.5 ( Fig.…”
Section: Introductionmentioning
confidence: 95%
“…Unfortunately, studies to date have yielded a confusing amalgam of possible roles for USP22 in oncogenesis. Several studies have focused on potential roles for USP22 in regulating cell cycle progression through effects on oncogenes such as BMI1 (Liu et al, 2012), c-MYC (MYC) (Zhang et al, 2008a), SIRT1 (Lin et al, 2012), cyclin B1 (Lin et al, 2015), cyclin D1 (Gennaro et al, 2018) and KDM1A (Zhou et al, 2016), or on tumor suppressors such as p53 (Trp53) (Ding et al, 2015;Lin et al, 2012;Lv et al, 2011). The previously defined 11-gene 'death from cancer' signature that includes USP22 also includes BMI1 and downstream targets of this polycomb group protein.…”
Section: Examination Of Monoubiquitination Of Histone H2b (H2bub1) Inmentioning
confidence: 99%
“…Recently, several deubiquitinases have been reported to be involved in cell cycle progression. USP2 and USP22 can stabilize cyclin D1 to promote cell cycle progression [16,17]. A recent study also revealed that a small molecule, ML364, can inhibit USP2 to promote degradation, leading to cell cycle arrest [18].…”
Section: Usps Are Involved In Cell Cycle Progressionmentioning
confidence: 99%
“…CCND1 has an A/G polymorphism at nucleotide 870, at the splice donor site of the exon 4-intron 4 boundary. This polymorphism leads to alternative splicing, generating a cyclin D1 variant called cyclin D1b [50] ( Figure 1B). The mature cyclin D1b transcript includes exon 4 and intron 4.…”
Section: Cyclin D1 Accumulates In the Nucleus And/or In The Cytoplasmmentioning
confidence: 99%